2018
DOI: 10.4155/bio-2017-0228
|View full text |Cite
|
Sign up to set email alerts
|

Novel Automated Immune Turbidimetric Assay for Routine Urinary Cystatin-C Determinations

Abstract: Aim: There is no commercially available urinary cystatin-C (u-CYSC) test in the market. Therefore, we optimized and validated an automated immune turbidimetric test for u-CYSC measurements and investigated u-CYSC concentrations in acute and chronic diseases which might lead to renal tubular disorders. Materials & methods: A particle-enhanced immune turbidimetric assay was adapted and validated on a Cobas 8000/c502 analyzer. Urine samples of different patient groups were also analyzed. Results: Our method s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 28 publications
2
16
0
1
Order By: Relevance
“…Another study of approximately 1500 children and adults after cardiac surgery also found no association of cystatin C with AKI . Further investigation of cystatin C in larger population studies is necessary to determine its value as a biomarker for AKI, and the recent development of validated, sensitive, and automated assays to measure urine cystatin C may help with this effort . Currently, however, cystatin C is not validated as a diagnostic biomarker for AKI.…”
Section: Limitations Of Cystatin C As a Gfr Biomarkermentioning
confidence: 99%
“…Another study of approximately 1500 children and adults after cardiac surgery also found no association of cystatin C with AKI . Further investigation of cystatin C in larger population studies is necessary to determine its value as a biomarker for AKI, and the recent development of validated, sensitive, and automated assays to measure urine cystatin C may help with this effort . Currently, however, cystatin C is not validated as a diagnostic biomarker for AKI.…”
Section: Limitations Of Cystatin C As a Gfr Biomarkermentioning
confidence: 99%
“…Additionally, u‐ORM/u‐TP and u‐ALB/u‐TP ratios were also determined to examine the proportional change of ORM and albumin among urinary proteins. To check renal glomerular and tubular function, cystatin‐c was measured from serum samples by a commercial kit (Roche, Diagnostics GmbH) and from urine by our recently described automated turbidimetric assay …”
Section: Methodsmentioning
confidence: 78%
“…Renal function (glomerular and tubular) was normal in each group based on serum and urinary cystatin‐c (u‐CYSC) measurements. U‐CYSC/u‐CREAT showed difference only between adult control and active CD groups; however, all patients had u‐CYSC/u‐CREAT values within the reported reference range …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations